PENGARUH PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN DAN NILAI PERUSAHAAN Studi Kasus pada Pasar Modal Syariah - Sutrisno Sutrisno (Business Management Journal, 2017)
The purpose of this study is to examine the effect of profitability on dividend policy and firm value. Dividend policy is proxied by the dividend per share, while profitability is proxied by return on equity, return on assets and net profit margin. Firm value measured by price-to-book value ratio. We use firm size as a controlle varable. The population in this study are the companies that are members of the Jakarta Islamic Index (JII). Therefore there are only 30 companies that listed in JII, then all of companies were taken as samples with a four-year observation period (2008-2011). To analyze the data, we use multiple regression that supported by eviews program.The results showed that first profitability variables that significantly affect dividend policy is the return on assets and return on equity, while net profit margin and firm size does not affect the dividend policy. Second, dividend policies significantly affect the firm value. While profitability variables that significantly affect the firm value is the return on equity and return on assets, but net profit margin and firm size does not affect to firm value.